Influence of Product Quality, Brand Loyalty and Social Media Influencers on Purchase Decisions of Samsung Smartphone Product - Ridhowati, Lutfi -; Budi Utaminingtyas, Rara Ririn; Taviyastuti, Taviyastuti - (Politeknik Negeri Semarang, 2024)
The purpose of this study is to assess the impact of Product Quality, Brand Loyalty, and Social Media Influencers on the Purchase Decision of Samsung smartphone customers in Semarang. This study employs quantitative research methodologies and includes a sample of 120 Samsung smartphone users from Semarang City. Purposive sample was utilized as the sample approach instead of probability sampling. Data were obtained using a questionnaire that has been validated and reliable. Classical assumption tests, multiple regression analysis, the F test, coefficient of determination, and the t test are all methods for analyzing data. This study used SPSS version 25, resulting the coefficient of determination (R2) is 0.559, or 55.9%, with the remainder explained by factors not investigated in this study. The findings revealed that Product Quality, Brand Loyalty, and Social Media Influencers had a favorable and substantial influence on Purchase Decisions, both partially and concurrently.